EDUKASI KESEHATAN DALAM OPTIMALISASI SKRINING KESEHATAN PENYAKIT TIDAK MENULAR PADA SISWA SMAN 8 PADANG - Ayulia Fardila Sari ZA; Shelvy Haria Roza (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Non-communicable diseases (NCDs) such as hypertension, diabetes mellitus, and cancer are the leading causes of death in Indonesia. Preventive efforts through health screening remain low, especially among adolescents who are increasingly exposed to unhealthy lifestyles. This community service activity aimed to optimize self-screening practices among high school students through health education on NCDs and a simulation of the Mobile JKN application. The program was conducted at SMAN 8 Padang from September 6 to 20, 2024, involving 40 tenth-grade students. The intervention included planning, implementation, and evaluation phases. Activities consisted of health education sessions, distribution of educational materials (leaflets and screening guidebooks), and a simulation of digital self-screening. Evaluation was carried out through oral surveys of five randomly selected students. All students demonstrated an understanding of the material and were able to perform the screening simulation correctly. They also expressed commitment to becoming health ambassadors in their families and communities. This initiative aligns with the Health Belief Model and school-based health promotion approaches, while also supporting Indonesia's national digital health transformation through the SATU SEHAT policy. The activity proved effective in increasing students’ awareness of early detection and prevention of NCDs. It is recommended that this program be replicated in other schools and further developed by involving teachers and providing digital learning media for sustainable impact.